Integrated Islamic Elementary School Uses Spiritually Charged Reading-Writing Resources for English Language Learning - Zulhi Amalia, Taranindya; Rini Dwi Susanti (Institut Agama Islam Negeri Madura, 2025)
This study aims to describe the utilization of spiritually nuanced reading and writing resources for learning English in Integrated Islamic Elementary Schools, as well as its impact on students' language skills. The research used a qualitative approach with field methods through interviews, observation, and documentation. The results showed that the implementation of an independent curriculum is supported by regular training for teachers, implemented in grades I and IV with the concept of differentiation, channelling students' talents and interests through extracurricular activities. This curriculum adopts Active Deep Learner Experience and innovates Individualization, Interaction, Observation, Reflexion with an integrated approach. The utilization of learning resources includes teachers, textbooks, worksheets, technology devices (microphones, amplifier, LCD projectors, laptops), language laboratories, and English Club activities. The textbooks published are tailored to Islamic spiritual values and student needs. The positive impact of this curriculum is the increased creativity of teachers in integrating modern learning resources with science and technology and strengthening students' interests and talents through personalized and innovative learning. The concept of differentiation is effective in attracting students' interest in learning.